The dysregulation of immune cells induced by uric acid: mechanisms of inflammation associated with hyperuricemia and its complications - Li, Delun; Yuan, Siyu; Deng, Yiyao; Wang, Xiaowan; Wu, Shouhai; Chen, Xuesheng; Li, Yimeng; Ouyang, Jianting; Lin, Danyao; Quan, Haohao; Fu, Xinwen; Li, Chuang; et al. (Frontiers in Immunology, 2023)
Changes in lifestyle induce an increase in patients with hyperuricemia (HUA), leading to gout, gouty arthritis, renal damage, and cardiovascular injury. There is a strong inflammatory response in the process of HUA, while dysregulation of immune cells, including monocytes, macrophages, and T cells, plays a crucial role in the inflammatory response. Recent studies have indicated that urate has a direct impact on immune cell populations, changes in cytokine expression, modifications in chemotaxis and differentiation, and the provocation of immune cells by intrinsic cells to cause the aforementioned conditions. Here we conducted a detailed review of the relationship among uric acid, immune response, and inflammatory status in hyperuricemia and its complications, providing new therapeutic targets and strategies.